Komparasi Kehujahan Hadis Shahih, Hasan, Dhaif, dan Maudhu’ - Ngampo, Muhammad Ali (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This article aims to find out the definition, division, proof, and hadith books of Sahih, Hasan, Daif, and Maudhu'. In this article the researcher uses a qualitative research method (library research). Hadith is a guide and guidance for the life of a Muslim and functions as an explanation of the verses of the Qur'an. In terms of quality, hadith are divided into three types; including authentic hadith, hasan hadith, and dhaif hadith. An authentic hadith is a hadith whose sanad is continued through the transmitter of a just and habitual person from a just and habitual person, until the end, is not shaz and is not famous illat, while a hasanic hadith is a hadith whose sanad is continuous, by a writer who is 'just but less accurate. dhabitan and avoids syaz and illat, while dhaif hadith is a hadith that meets the requirements of authentic hadith and does not meet the requirements of hasan hadith. The mudhu' hadith is something that was created and fabricated and then attributed to the Prophet falsely.